Direct Evidence of the Hybrid Nature of Extreme-ultraviolet Waves and the Reflection of the Fast-mode Wave - Ramesh Chandra; P. F. Chen; Pooja Devi (The Astrophysical Journal, 2024)
We performed an analysis of the extreme-ultraviolet (EUV) wave event on 2022 March 31. The event originated from active region (AR) 12975 located at N13W52 in the field of view of the Atmospheric imaging Assembly (AIA) and exactly at the west limb viewed by the EUV Imager (EUVI) of the Solar Terrestrial Relations Observatory-Ahead (STEREO-A) satellite. The EUV wave was associated with an M9.6 class flare. The event was also well observed by Mauna Loa Solar Observatory and COR1 coronagraphs. We revealed here evident coexistence of two components of EUV waves in AIA as well as in EUVI images, i.e., a fast-mode wave and a nonwave, which was predicted by the EUV wave hybrid model. The speeds of the fast-mode and nonwave EUV wave components in AIA vary from ∼430 to 658 km s ^−1 and ∼157 to 205 km s ^−1 , respectively. The computed speeds in STEREO-A for the fast-mode wave and nonwave components are ∼520 and ∼152 km s ^−1 , respectively. Another wave emanated from the source AR and interacted with ambient coronal loops, showing evident reflection in the EUV images above the solar limb. The speed of the reflected wave in the plane of the sky is ∼175 km s ^−1 . With the precise alignments, we found that the fast-mode EUV wave is just ahead of the coronal mass ejection (CME), and the nonwave component is cospatial with the frontal loop of the accompanied CME. The event also showed stationary fronts.